REKONSTRUKSI TEKNOLOGI INTEGRALISTIK AKUNTANSI SYARI’AH: SHARFATE VALUE ADDED STATEMENT - Mulawarman, Aji Dedi; Triyuwono, Iwan; Ludigdo, Unti (UI Scholars Hub, 2007)
The objective of the research is to formulate Shari’ate Value Added Statement. Formulation is conducted by utilizing Integrated Islamic Hyperstructuralism Methodology. In that methodology, conventional concept of value added and Baydoun and Willett’s (1994) concept of value added are refined by Shari’ate Accounting. The result is then refined by Islamic Technosystem to generate Shari ’ate Value Added Statement. The major result shows that zakat becomes a substance of Shari’ate Value Added. This means that Shari’ate Value Added is actually economic (physical) value added (zak%) which is always purificated spiritually (tazkiyah). The purificated economic value added (zaka) is called as zakka (or it is the same as Shari ’ate Value Added). Both zakka and tazkiyah is extracted from the values and concepts of Abd’ Allah and Khalifatullah fil ardh. The consequence of the major result are : (1) that the sources of value added in the Shari’ate Value Added Statement should be acquired based on God’s commands (halal, thoyib and eliminating riba,), and (2) the distributions of the value added should be based on mashlaha and ‘Adalah (God ’s Justice).